Laser welding of H-phase strengthened Ni-rich NiTi-20Zr high temperature shape memory alloy. (April 2021) - Oliveira, J.P.; Shen, Jiajia; Escobar, J.D.; Salvador, C.A.F.; Schell, N.; Zhou, N.; Benafan, O.
Abstract: Laser welding of a Ni-rich NiTi-20Zr (at.%) high temperature shape memory alloy was performed. The starting base material was aged for 3 h at 550 °C followed by air cooling prior to welding to induce H-phase precipitation. Advanced microstructure characterization encompassing scanning and transmission electron microscopy, coupled with synchrotron X-ray diffraction, were used. Defect-free welds were obtained with a conduction welding mode. The weld thermal cycle altered the microstructure across the heat affected and fusion zones of the joints. The heat affected zone exhibited partial H-phase dissolution, causing a decrease in hardness. In the fusion zone, the H-phase fully dissolved, and the non-equilibrium rapid solidification conditions prevented the H-phase from re-precipitating during cooling, leading to a microstructure resembling that of an as-cast alloy with the same material composition. Mechanical testing revealed that the laser welded samples sustained stresses in the order of 500 MPa and exhibited stress-strain responses comparable to those of the unwelded base material. Thus, this initial study shows new possibilities for using advanced laser joining methods in these alloys. Graphical abstract: Unlabelled Image Highlights: Laser welding of an H-phase strengthened NiTi-20Zr high-temperature shape memory alloy was successfully performed. The aged NiTi-20Zr experienced partial H-phase dissolution in the heat-affected zone. The welded joints sustain stresses typically used in actuator applications (up to 500 MPa).